A systematic review of therapeutic modalities used in sleep bruxism - May Wathiq Al-Khudhairy (Wolters Kluwer Medknow Publications, 2015)
Aim: Sleep bruxism (SB) has been present for over a century. There are many treatment modalities in the literature. The objective of this systematic review of randomized controlled clinical therapeutic trials of SB in adults diagnosed by clinical and/or electromyogram and/or polysomnography of SB is to elucidate the most effective of treatment modalities via documentation of the levels of evidence. Materials and Method: This review conducted electronically on PubMed included only English Full text human clinical trials with or without randomization. Twenty-one articles were included in this review. The therapeutic modalities of SB were classified into behavioral therapy, appliance therapy, local pharmacotherapy, and systemic pharmacotherapy. Each article was further allotted a level of evidence. Results: This review suggests that Oral appliances expressed the most positive outcome on SB episodes per hour of sleep. Conclusion: There is still not sufficient evidence to support behavioral and pharmaco-therapeutic approach